Hop Phytochemicals and Their Potential Role in Metabolic Syndrome Prevention and Therapy - Dostálek, Pavel; Karabín, Marcel; Jelínek, Lukáš (Molecules, 2017)
Historically, hop cones (Humulus lupulus) have been used since ancient times as a remedy for many ailments and, as a source of polyphenols and bitter acids, is very effective in the treatment of metabolic syndrome (MS). Hop flavonoids, particularly xanthohumol (XN), are substances with hypoglycemic, antihyperlipidemic, and antiobesity activities. Iso-α-acids (IAA) and matured hop bitter acids (MHBA) improve health by influencing lipid metabolism, glucose tolerance, and body weight. The modulatory effect of IAA and MHBA on lipid metabolism may also be responsible for a loss in body weight. These results suggest promising applications for IAA, MHBA, and XN in humans, particularly in the prevention of diet-induced obesity and diabetes.
Keywords: Flavonoids; Phytochemicals; tělesná hmotnost; Humulus; flavonoidy; Humans; Molecular Structure; glukózový toleranční test; metabolický syndrom; Propiophenones; propiofenony; fytonutrienty; Glucose Tolerance Test; metabolismus lipidů; lidé; Body Weight; Lipid Metabolism; Metabolic Syndrome; molekulární struktura